Implementation of Criminal Profiling as a Supporting Tool for Investigators of Children as Perpetrators of Violent Crimes - Cicilia Tan; Rasdi Rasdi (Universitas Negeri Semarang, 2026)
Children committing violent crimes has been rampant in Indonesia in recent months. The emergence of klitih, a phenomenon where teenagers commit crimes on the streets, has occurred in several regions of Indonesia, such as Yogyakarta and Semarang, as well as several other areas. Law enforcement for children and adults is very different; children must receive humane, comprehensive treatment that prioritizes their interests. Investigators as law enforcers must understand the social, psychological, and environmental conditions of children who commit violent crimes. The law is constantly evolving with the times, one example being criminal profiling, which aims to analyze the behavior patterns, mental conditions, social conditions, and characteristics of criminals. The practice of law enforcement using criminal profiling methods can help investigators understand the mental and social conditions of children and the characteristics that underlie their behavior as perpetrators of crime.